2013
DOI: 10.1111/trf.12169
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of expanded erythroid cells for autologous transfusion for anemia of prematurity

Abstract: This explorative study showed that fairly pure autologous erythroid-expanded cell populations could be obtained by a simple culture method, which should be optimized. Future challenges comprise obtaining ex vivo enucleation of RBCs with the use of a minimal manipulating approach, which can add up to autologous RBCs derived from CB in the treatment of anemia of prematurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The enucleation efficiency obtained by our culture was comparable to those by other groups with a co-culture-free system for erythrocyte differentiation starting from cord blood-derived progenitor cells [3537]. In our study, filtration removed approximately 75% of cells, even though only 53% were nucleated.…”
Section: Discussionsupporting
confidence: 82%
“…The enucleation efficiency obtained by our culture was comparable to those by other groups with a co-culture-free system for erythrocyte differentiation starting from cord blood-derived progenitor cells [3537]. In our study, filtration removed approximately 75% of cells, even though only 53% were nucleated.…”
Section: Discussionsupporting
confidence: 82%
“…More recently, data have been published on the terminal differentiation of HSCs, which proved successful without a supportive cell layer. The expansion fold rate without a feeder layer was higher (~37 000) than with a feeder layer (~29 000), but the enucleation rates were ~68% and ~90%, respectively (Giarratana et al ., , ), while another study obtained a majority of erythroblasts and observed no reticuloctyes or erythrocytes after 21 days of culture (Khodabux et al ., ). The efficiency of enucleation is important in each of these cases, as is the effect this will have on the widespread potential of translating this redesigned culture into the clinic.…”
Section: The Stem Cell Environmentmentioning
confidence: 99%
“…Recent studies have elucidated the complex mechanisms underlying late-stage erythropoiesis by examining the in vitro generation of stem cell-derived red blood cells (RBCs). However, there are problems recapitulating this process in vitro, the main issues being delayed maturation, inefficient enucleation, low viability, dysregulated apoptosis, and dysplastic cell features, such as variable cell size and multi-nucleation [ 1 , 2 , 3 , 4 ]. These effects are thought to be due to the absence of certain stimulatory factors and signals, and to dysregulated autophagy.…”
Section: Introductionmentioning
confidence: 99%